Marine managed areas and fisheries. - Johnson, Magnus L.; Sandell, Jane (Advances in marine biology, 2014)
Advances in Marine Biology has been providing in-depth and up-to-date reviews on all aspects of marine biology since 1963--over 40 years of outstanding coverage! The series is well known for its excellent reviews and editing. Now edited by Michael Lesser (University of New Hampshire, USA) with an internationally renowned Editorial Board, the serial publishes in-depth and up-to-date content on many topics that will appeal to postgraduates and researchers in marine biology, fisheries science, ecology, zoology, and biological oceanography. Volumes cover all areas of marine science, both applied and basic, a wide range of topical areas from all areas of marine ecology, oceanography, fisheries management and molecular biology and the full range of geographic areas from polar seas to tropical coral reefs. This volume, with an introduction by Ray Hilborn, will present the latest views on the use of MPAs or Marine Managed Areas for fisheries management. It will contain a wide range of case studies including the Chagos archipelago, South Georgia, the Caribbean, the North Sea, Florida, Hawaii, Great Barrier Reef, California, Mediterraneanand the Phoenix Islands Protected Area. It is the intention of the editors that the volume presents a series of evidence based rather than advocacy driven contemporary reviews. AMB volumes solicit and publish review articles on the latest advances in marine biology Many of the authors of these review articles are the leading figures in their field of study and the material is widely used by managers, students and academic professionals in the marine sciences.